PENGARUH KONSUMSI MAKANAN GENERASI Z TERHADAP NIAT UNTUK PENGURANGAN LIMBAH MAKANAN RESTORAN DI SURABAYA - Hanjaya Siaputra; Natalia Chealsea; Michelle Angela (Institute of Research and Community Outreach - Petra Christian University, 2022)
The purpose of this research is to analyze the influence of generation Z food consumption towards food waste reduction intention in restaurants in Surabaya with attitude, subjective norms and perceived behavioral control as the mediating variables. This research was conducted by distributing questionnaires to 241 respondents, then analyzed using descriptive statistical analysis techniques with Partial Least Square (PLS) software. The result showed a positive, but insignificant relationship between generation Z food consumption and food waste reduction intention. Attitude and subjective norms were not proven to have mediating effect between the two variables, whereas perceived behavioral control were proven to have mediating effect. Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh konsumsi makanan generasi Z terhadap food waste reduction intention dalam restoran di Surabaya dengan variabel mediasi attitude, subjective norms, dan perceived behavioral control. Penelitian ini dilakukan dengan menyebarkan kuesioner kepada 241 responden dan dianalisis menggunakan teknik analisa statistik deskriptif dengan menggunakan software Partial Least Square (PLS) dalam proses pengolahan datanya. Hasil yang diperoleh dalam penelitian ini menunjukkan adanya hubungan yang positif tetapi tidak signifikan antara food consumption generasi Z terhadap food waste reduction intention. Kemudian attitude serta subjective norms tidak terbukti sebagai variabel yang memediasi hubungan antara food consumption generasi Z terhadap food waste reduction intention, sedangkan perceived behavioral control terbukti sebagai variabel yang memediasi hubungan antara food consumption generasi Z terhadap food waste reduction intention.